The Effects of Majoring in Political Science on Political Efficacy. Issue 1 (2nd January 2017) - Dominguez, Casey B. K.; Smith, Keith W.; Williams, J. Michael
ABSTRACT: This study tests, and finds support, for the hypotheses that a student who majors in political science will have stronger feelings of political competence and will be more willing to engage in hypothetical political actions than two peer groups: (a) those who major in other fields and (b) those who show an interest in politics but have not studied it. In a study of 1, 083 undergraduates at two different universities, we find that senior political science majors have higher feelings of internal political efficacy than comparison groups and are more willing than their peers or than interested freshmen to say that they would engage in meaningful political action, especially joining organized groups.